The Implementation of Group Learning Discussion to Speaking Skills of Management Students in Business Presentation - Kaloeti, Ade Kristianus (EQUILIBRIUM - Jurnal Bisnis dan Akuntansi, 2024)
This study aims to determine the effect of Group Discussion Learning on the English speaking ability of Management study program students in Business presentations. The population in this study were active students of Management study program in the first semester of batch 2023. 35 students were selected by using purposive sampling technique. The data were obtained through experimental method approach where post-presentation was given after treatment of Group Discussion Learning (GDL) and pre-presentation. The result of the study is that there is a significant effect of GDL learning method on English speaking ability of Management study program students in business presentation.